Optimization of Microwave-Assisted Alkali Pretreatment for Enhancement of Delignification Process of Cocoa Pod Husk - Maktum Muharja; Rizki Fitria Darmayanti; Bekti Palupi; Istiqomah Rahmawati; Boy Arief Fachri; Felix Arie Setiawan; Helda Wika Amini; Meta Fitri Rizkiana; Atiqa Rahmawati; Ari Susanti; Ditta Kharisma Yolanda Putri (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
In this study, the optimization of microwave-assisted alkaline (MAA) pretreatment is performed to attain the optimal operating parameters for the delignification of cocoa pod husk (CPH). The MAA performance was examined by heating the CPH solid with different particle sizes (60–120 mesh) and NaOH solution with a different sample to a solvent (SS) ratio (0.02–0.05 g/L), for short irradiation time (1–4 min). Box-Behnken Design (BBD) was utilized to optimize the percentage of lignocellulose composition changes. The results show that by enlarging particle size, the content of lignin and cellulose decreased while hemicellulose increased. By prolong irradiation time, the content of lignin and hemicellulose decreased while cellulose elevated. On the other hand, increasing the SS ratio was not significant for hemicellulose content changes. From FTIR and SEM characterization, the MAA drove the removal of lignin and hemicellulose of CPH and increased cellulose slightly. Supported by kinetic study which conducted in this work, it was exhibited that MAA pretreatment technology is an effective delignification method of CPH which can tackle the bottleneck of its commercial biofuel production. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).